Application of next generation sequencing technology on contamination monitoring in microbiology laboratory - Yan Xiao; Li Zhang; Bin Yang; Mingkun Li; Lili Ren; Jianwei Wang (Elsevier, 2019)
The surveillance and prevention of pathogenic microbiological contamination are the most important tasks of biosafety management in the lab. There is an urgent need to establish an effective and unbiased method to evaluate and monitor such contamination. This study aims to investigate the utility of next generation sequencing (NGS) method to detect possible contamination in the microbiology laboratory. Environmental samples were taken at multiple sites at the lab including the inner site of centrifuge rotor, the bench used for molecular biological tests, the benches of biosafety cabinets used for viral culture, clinical sample pre-treatment and nucleic acids extraction, by scrubbing the sites using sterile flocked swabs. The extracted total nucleic acids were used to construct the libraries for deep sequencing according to the protocol of Ion Torrent platform. At least 1G raw data was obtained for each sample. The reads of viruses and bacteria accounted for 0.01 ± 0.02%, and 77.76 ± 12.53% of total reads respectively. The viral sequences were likely to be derived from gene amplification products, the nucleic acids contaminated in fetal bovine serum. Reads from environmental microorganisms were also identified. Our results suggested that NGS method was capable of monitoring the nucleic acids contaminations from different sources in the lab, demonstrating its promising utility in monitoring and assessing the risk of potential laboratory contamination. The risk of contamination from reagents, remnant DNA and environment should be considered in data analysis and results interpretation.